A Study on the Issues and Possible Solutions for Archaeological Heritage Management in the Jaffna Peninsula - Sivaruby, S. (University of Jaffna, 2021)
The archaeological heritage sites and monuments of a nation are regarded as reliable evidence which form the ancient and continuous history and culture of each racial group which reside there. These archaeological heritages illustrate that Jaffna which has been identified as a unique region since ancient times in the history of Sri Lanka has a continuous history of not less than 2500 years. They also reflect the archaeological, historical, social, religious, scientific, technical, architectural and artistic values of the people of the area. The objectives of this research are to identify the issues and challenges encountered in the protection of the remaining Heritage Monuments from extinction and analyzing the future measures required to be carried out in the future for their protection. In view of achieving these objectives, the research methodologies used in this research include the direct observation of heritage monuments, collection of data through face to face interviews and the collection of secondary information through literary works. In terms of the Antiquities Amendment Act No. 24 of 1988 of Sri Lanka, all lands, buildings and trees which hold archaeological and historic value daring back more than 100 years are declared as heritage monuments. However, it could be observed that the heritage monuments which have been registered accordingly and the identified and unidentified heritage monuments have been subjected to extinction due to several issues. As such since several issues are encountered in the protection of archaeological heritages, the need of time is that protection measures should be carried out on the basis of the best possible planning. Thereby, this research sheds light on the overall importance of the archaeological heritages in the Jaffna Peninsula and attempts to elicit the emerging challenges in heritage preservation in this region. Moreover, this paper outlines major strategic mechanisms required to overcome these constraints to preserve our cultural heritage which is nothing but the true reflection of our rich cultural past.
Keywords: Archaeological Heritage; Heritage Issues; Heritage Management; Heritage Values; Heritage Preservation